Synthesis, characterisation and binding evaluation of new 6-amidinoindole compound as the potential heme binder - Noraisyah Abdul Kadir Jilani,; Oka, Natsuhisa; Ando, Kaori; Siti Aishah Hasbullah, (Universiti Kebangsaan Malaysia, 2023)
In this study, the new compound 6-amidinoindole 3 were synthesized by hydrogenating the amidoxime unit in a high yield. The compound was characterized by FTIR, 1H NMR, 13C NMR and ESI-MS. The binding of the compound towards heme was evaluated using absorption spectroscopy. The studies found that the association constant (log K) is 3.90. The binding strength indicated the ligand’s possibility to interact significantly with heme and acted as a binder to the malaria parasite. In silico hemozoin docking was performed to gain insight into the mode of action. The docked score is -8.3 kcal/mol, indicated the possible inhibition of hemozoin. This study could serve as the basis for the future development of malaria sensors and antiplasmodial activity.